2022
DOI: 10.3390/electronics11071151
|View full text |Cite
|
Sign up to set email alerts
|

Human Detection in Aerial Thermal Images Using Faster R-CNN and SSD Algorithms

Abstract: The automatic detection of humans in aerial thermal imagery plays a significant role in various real-time applications, such as surveillance, search and rescue and border monitoring. Small target size, low resolution, occlusion, pose, and scale variations are the significant challenges in aerial thermal images that cause poor performance for various state-of-the-art object detection algorithms. Though many deep-learning-based object detection algorithms have shown impressive performance for generic object dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 53 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…Consequently, Liu et al (2016) proposed a Single Shot MultiBox Detector (SSD). The SSD algorithm uses multi-scale features and default anchor boxes to detect the presence of multi-scale objects in the scene in a single step ( Akshatha et al, 2022 ). Its network structure is shown in Supplementary Figure 1B .…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, Liu et al (2016) proposed a Single Shot MultiBox Detector (SSD). The SSD algorithm uses multi-scale features and default anchor boxes to detect the presence of multi-scale objects in the scene in a single step ( Akshatha et al, 2022 ). Its network structure is shown in Supplementary Figure 1B .…”
Section: Methodsmentioning
confidence: 99%
“…Object detection methods can be divided into two categories: two stage and one stage. In the two-stage object detection, the objects are first localized and then classified, and the representative algorithms are R-CNN [11], Fast R-CNN, and R-FCN [12]. One-stage object detection regards object detection as a regression problem and performs localization and classification at the same time.…”
Section: Related Workmentioning
confidence: 99%
“…Based on the results, we can see that the proposed methodology has higher classification accuracy values than other deep learning approaches in terms of recognition rate Recall, Precision, and F-Score. The achieved F-Score for the proposed technique is 95.34%, compared to 90.85% for faster R-CNN [16], 84.49% for YOLOv3 [17], 68.47% for DCNN [15], and 92.50% for SSD [14]. The proposed method's acquired Precision is quite similar to SSD [14]'s precision.…”
Section: Performance Metricsmentioning
confidence: 73%
“…To identify human targets in aerial view thermal pictures, Akshatha et al [14] suggested Faster R-CNN and single-shot multi-box detector (SSD) algorithms with various backbone networks. To achieve this, two common aerial thermal datasets with variously sized human objects ResNet50, Inception-v2, and MobileNet-v1 are taken into consideration.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation